POST - CERVICAL UTERINE TORSION IN A BUFFALO- A CASE STUDY - DEORI, S; KUMAR, RAVINDRA; JAGLAN, PRADEEP; DEBNATH, S; SARKER, M; DAS, G K; SHANKER, UMA (The Indian Journal of Animal Reproduction, 2023)
A case of right side post cervical uterine torsion of more than 180° in a plUriparous buffalo and it successful management is reported in this communication.
Keywords: Dystocla; Torsion; Buffalo